ПУБЛИЦИСТИКАНЫҢ ЖЕККЕ МЕТОДЛАРЫ (1-мақала) - Машарипова, Т.Ж. (SCIENCE and SOCIETY, 2016)
The article is devoted to the description of publicistic methods. The most popular classification is a three-level classification of methods, according to which there are overall, general and private methods. The overall method is dialectics, the general method is the mais operative actual expressive reflection. There are many private methods, their systematization depends on the author‘s approach: methods of topic choice, selection and working out facts, emotional colouring of texts and others
Keywords: publicistics; newspaper; journal; classification of methods; dialectics; reflexion; Uzbekistan; Karakalpakstan